2019
DOI: 10.1001/jama.2019.5357
|View full text |Cite
|
Sign up to set email alerts
|

Association of Changes in Air Quality With Incident Asthma in Children in California, 1993-2014

Abstract: IMPORTANCE Exposure to air pollutants is a well-established cause of asthma exacerbation in children; whether air pollutants play a role in the development of childhood asthma, however, remains uncertain. OBJECTIVE To examine whether decreasing regional air pollutants were associated with reduced incidence of childhood asthma. DESIGN, SETTING, AND PARTICIPANTS A multilevel longitudinal cohort drawn from 3 waves of the Southern California Children's Health Study over a period of air pollution decline. Each coho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
102
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(110 citation statements)
references
References 37 publications
2
102
0
1
Order By: Relevance
“…Other significant differences were found between grids without monitors and grids with monitors for poverty percent and population density for all case and control groups (all p's ≤ 0.05). Monitor-No 6.0 (5.9-6.1) * 6.0 (6.0-6.1) * 6.4 (6.3-6.5) * 6.4 (6.3-6.4) * 4 Significant difference between no monitor versus monitor within poverty, p ≤ 0.05. 5 Significant difference between no monitor versus monitor within population density (Population, L 10 ), p ≤ 0.05.…”
Section: Cases and Controlsmentioning
confidence: 99%
See 2 more Smart Citations
“…Other significant differences were found between grids without monitors and grids with monitors for poverty percent and population density for all case and control groups (all p's ≤ 0.05). Monitor-No 6.0 (5.9-6.1) * 6.0 (6.0-6.1) * 6.4 (6.3-6.5) * 6.4 (6.3-6.4) * 4 Significant difference between no monitor versus monitor within poverty, p ≤ 0.05. 5 Significant difference between no monitor versus monitor within population density (Population, L 10 ), p ≤ 0.05.…”
Section: Cases and Controlsmentioning
confidence: 99%
“…The adverse effects of PM 2.5 on the respiratory-cardiovascular system have been repeatedly confirmed [1][2][3][4][5][6][7][8][9][10][11][12]. Epidemiologic studies that assess exposure risk to different ambient PM 2.5 concentration levels have relied on the U.S. Environmental Protection Agency's (EPA) network of ground-based ambient air pollutant monitors [4,[13][14][15][16]. Ambient air monitors are not equally spatially distributed, and most make measurements every 3 or 6 days [13,[16][17][18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On average, approximately 25-30% of PM 2.5 in the region is attributed to primary vehicle emissions and~15% to other mobile sources, as well as a similar contribution from stationary sources (e.g., industrial facilities) [9,10]. Children are particularly vulnerable to the adverse impacts of ambient air pollution, in part due their rapid growth, developmental vulnerability, greater exposure to air pollutants compared with adults, and immature immune systems [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of asthma has been increasing worldwide for at least three decades, without any definite reason. Recent evidence suggested that this increase of asthma cases might be linked to urban air pollution, with the fact that more and more people are attracted to living in cities [1][2][3][4][5]. According to the WHO, 30% of all child deaths before the age of 5 were due to asthma caused by polluted air (http://www.who.int/mediacentre/news/releases/2017/pollution-child-death/en/).…”
Section: Introductionmentioning
confidence: 99%